Atypical lignification in eastern leatherwood (Dirca palustris). Issue 3 (3rd February 2020) - Mottiar, Yaseen; Gierlinger, Notburga; Jeremic, Dragica; Master, Emma R.; Mansfield, Shawn D.
Summary: Lignin is a complex phenolic biopolymer found mainly in the secondary cell walls of vascular plants, where it contributes to mechanical strength, water conduction, and plant defence. We studied the lignin of eastern leatherwood ( Dirca palustris ) because this slow‐growing woody shrub is known for its flexible stems. Various analytical techniques and microscopy methods were employed to examine the composition and distribution of lignin and structural polysaccharides in leatherwood xylem in comparison with trembling aspen ( Populus tremuloides ) and white spruce ( Picea glauca ). We found that leatherwood has low overall levels of lignin, a high syringyl lignin content, and a unique distribution of lignin. Most remarkably, the cell corners and middle lamellae remain unlignified in mature xylem. These findings help explain the flexibility of leatherwood and also call into question the classical model of lignification, which purports that lignin polymerization begins in the cell corners and middle lamellae. This atypical lignification regime vividly illustrates the diversity in plant secondary cell wall formation that abounds in nature and casts leatherwood as a new model for the study of lignin biogenesis.